KOMPOSISI JENIS DAN STRUKTUR KOMUNITAS SERTA KEANEKARAGAMAN JENIS VEGETASI DI AREAL CAGAR ALAM BUKIT TANGKILING: Composition, Structure and Plants Diversity in nature reserves of Bukit Tangkiling - Setiarno; Nisfiatul Hidayat; Bambang T.A.; Muhammad Luthfi S. (HUTAN TROPIKA, 2020)
The research was conducted in October 2019 in the Bukit Tangkiling Nature Reserve, Central Kalimantan, aiming to find out the type composition, the community structure, and vegetation diversity. This research method is a survey with combination method and carried out purposively in sampling with total sample plots of 60. The results showed that there were 58 species of plants (6 species unidentified) which included 11 species of understorey, 32 species of seedlings, 32 species of saplings, 31 species of poles, and 38 species of trees. Vegetation at the level of seedlings, saplings, poles, and trees in the Bukit Tangkiling Nature Reserve is dominated by Acacia mangium, while the understorey is dominated by nut grass and thatch. The similarity index of vegetation communities between two locations ranged from 41.860 - 73.684%, while that between growth rates ranged from 32.558 - 7.143%. Plant communities have diversity values (H’), richness values (R), and evenness values (E) ranging from low to moderate. The horizontal stand structure has different exposed diameters, forming an inverted “J” curve and is concentrated in diameter class 1019.99 cm, while vertically the individual population is concentrated in high class 5 - 9.99 m.Keywords: Composition, Heterogeneity, Similarity, Stand structure